Knowledge of telemedicine and its associated factors among health professional in Ethiopia: A systematic review and meta-analysis. - Adamu Ambachew Shibabaw; Alex Ayenew Chereka; Agmasie Damtew Walle; Addisalem Workie Demsash; Geleta Nenko Dube; Abiy Tasew Dubale; Sisay Yitayh Kassie; Gemeda Wakgari Kitil; Mesafint Zewold Jember; Chernet Desalegn Gebeyehu; Aster Temesgen Ariger; Eshetie Andargie Dires (PLoS ONE, 2024)
Introduction Telemedicine is a useful tool for decreasing hospital stress, patient suffering, ambulance needs, hospital anxiety, and costs while improving the standard of care. Nonetheless, the lack of awareness regarding telemedicine poses a barrier to its application, presenting several difficulties in underdeveloped nations like Ethiopia. This review evaluates Ethiopian-specific telemedicine knowledge and associated factors. Methods This systematic review was conducted using a search of several online databases in addition to the main databases, like Medline, PubMed, Scopus, and Science Direct. The writers have looked for, reviewed, and summarized information about telemedicine knowledge in the healthcare system. This study contained seven studies that examined telemedicine knowledge in the Ethiopian healthcare sector. Studies that followed the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA) were found using search engines. The investigation was carried out using STATA version 11. The indicator of heterogeneity (I2) was used to assess the level of heterogeneity among the included studies. The funnel plot was visually inspected, and Egger's regression test was run to check for publication bias. The pooled effect size of every study is estimated using a random-effect model meta-analysis. Results Examination of 2160 studies, seven studies involving 2775 health professionals, and seven out of the 2160 publications assessed satisfied the inclusion criteria and were added to the systematic review and meta-analysis. The pooled prevalence of Telemedicine knowledge was 45.20 (95% CI: 34.87-55.53). Whereas the pooled factor was computer training was 2.24 times (AOR = 2.24 (95%; CI: 1.64-3.08)), computer access was 2.07 times (AOR = 2.07 (95% CI: 1.50-2.87)), internet access was 3.09 times (AOR = 3.09 (95% CI: 1.34-7.13)), social media access were 3.09 times (AOR = 3.09(95%; CI: 1.34-7.13)), educational status degree and above were 2.73 times (AOR = 2.73; 95% CI: 0.85-8.82), Awareness were 3.18 times (AOR = 3.18 (95%; CI: 1.02-9.91)), Management support was 1.85 (AOR = 1.85 (95% CI: 01.25-2.75)), computer literacy were 2.90 times (AOR = 2.90 (95% CI: 1.81-4.64)), computer owner were 1.70 times (AOR = 1.70 (95% CI: 1.05-2.76)), male gender were 1.95 times (AOR = 1.95 (95% CI: 1.32-2.87)). Conclusion The overall pooled prevalence of telemedicine knowledge was low. Gender, education, management support, computer access, social media access, internet access, telemedicine awareness, and telemedicine training associated with telemedicine knowledge.